BUDAYA LITERASI DAN PENINGKATAN KETERAMPILAN BERPIKIR KRITIS DI ERA INDUSTRI 4.0: EKSPLORASI POTENSI KOLABORASI SEKOLAH DAN KOMUNITAS - Asnal Mala (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
The purpose of this study was to determine the role of teachers and principals in increasing literacy culture in Al-Chusnaini Klopohten Islamic Middle School-Sukodono-Sidoarjo as an effort to improve critical thinking skills, to determine the supporting and inhibiting factors in increasing literacy culture in Ak-Chusnaini Klopohten Islamic Middle School- Sukodono-Sidoarjo, knowing the strategies to increase literacy culture in increasing interest in reading at Al-Chusnaini Islamic Middle School Klopohten-Sukodono-Sidoarjo. This study uses a qualitative approach with this approach to produce descriptive data in the form of books (Risearch libraries) or verbally from people and observable behavior. The results of this study indicate that: 1) The role of the classroom teacher is as an educator, manager, administrator, supervisor, leader, innovator and motivator. 2) There are several supporting and inhibiting factors in developing a literacy culture. Supporting factors include the active role of students in school, support from parents of students. In addition, there are several inhibiting factors, namely: collection limitations, and the influence of technology. 3) In developing a literacy culture, teachers at SMP Islam Ak-Chusnaini Klopohten-Sukodono-Sidoarjo have several strategies used, including developing a library, providing fiction, non-fiction, and reference books. Development of reading areas, 15-minute reading program, Development of literacy-themed madrasah activity programs.